Chapter A method based on beach profile analysis for shoreline identification - Casarosa, Nicola (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Coastal erosion coupled with human-induced pressure has severely affected the coastal areas of the Mediterranean region. In this context, the Pisa coastal plain shows a long history of erosion, which started at the beginning of the nineteenth century. The work aims to provide a method and a software to extract the shoreline position. The algorithm is based on the variation of the topographic beach profile caused by the transition from water to sand. The algorithm is promoted by the release of a QGIS v3.x plugin uploaded on the official repository of the software.